Analisis Determinan Lingkungan dan Psikososial terhadap Pola Makan Remaja di Sekolah Asrama: Scoping Review - Aisyah Farah Nisrina; Diah Mulyawati Utari (Malahayati Nursing Journal, 2025)
ABSTRACT The adolescent phase is marked by a high prevalence of malnutrition, with dietary patterns being the primary determinant. The boarding school system is a unique environment that possesses the potential to create diverse factors significantly influencing adolescent dietary patterns. This review aims to identify and synthesize the determinants influencing adolescent dietary patterns in boarding schools, specifically focusing on environmental and psychosocial determinants. This study utilized a scoping review methodology based on the PEO (Population, Exposure, Outcome) framework. The systematic search was conducted between August-September 2025, adhering to the PRISMA-ScR (PRISMA Extension for Scoping Reviews) guidelines, resulting in seven articles for analysis. The review identified school policy as the most dominant environmental determinant, where inadequate meal frequency triggered compensatory over snacking. Furthermore, psychosocial factors such as peer influence and body image interact with the environment to promote unhealthy dietary practices, consequently increasing the risk of eating disorders and malnutrition. Dietary determinants in boarding school adolescents are a product of a complex interaction between the controlled environment and dynamic psychosocial factors. Future interventions must be multi-component, involving both the revision of food system policies and nutritional counselling support to optimize adolescent nutritional status. Keywords: Determinant, Dietary Patterns, Environment, Psychosocial, Boarding School.  ABSTRAK Fase remaja ditandai dengan tingginya prevalensi malnutrisi dan pola makan merupakan penentu utama. Sistem sekolah asrama (boarding school) merupakan lingkungan unik yang dapat menciptakan beragam faktor penentu yang signifikan mempengaruhi pola makan remaja. Tinjauan ini bertujuan untuk mengidentifikasi dan mensintesis determinan yang mempengaruhi pola makan remaja di sekolah asrama, khususnya determinan lingkungan dan psikososial. Studi ini menggunakan metode scoping review dengan kerangka PEO (Population, Exposure, Outcome). Pencarian dilakukan secara sistematis pada bulan Agustus-September 2025 dengan mengacu pada pedoman PRISMA-ScR (PRISMA Extension for Scoping Reviews), menghasilkan tujuh artikel yang dianalisis. Tinjauan mengidentifikasi kebijakan sekolah sebagai determinan lingkungan paling dominan dimana frekuensi makan yang kurang memadai memicu konsumsi camilan berlebihan sebagai kompensasi. Selain itu, faktor psikososial seperti pengaruh teman sebaya dan citra tubuh berinteraksi dengan lingkungan untuk mendorong praktik diet tidak sehat sehingga meningkatkan risiko gangguan makan dan malnutrisi. Determinan pola makan remaja di sekolah asrama adalah produk interaksi yang kompleks antara lingkungan yang terkontrol dan faktor psikososial yang dinamis. Intervensi di masa depan harus bersifat multi-komponen, melibatkan revisi kebijakan sistem penyelenggaraan makanan sekaligus dukungan konseling gizi guna mengoptimalkan status gizi remaja. Kata Kunci: Determinan, Lingkungan, Pola Makan, Psikososial, Sekolah Asrama.